RECIPROCAL TEACHING STRATEGY AND STUDENTS' READING COMPREHENSION : A Quasi Experimental Study in 8th Grade Students at a Junior High School in Cimahi - Rusmana, Kamelia Paska (2015)
The primary focus of this study is to investigate the effect of implementing Reciprocal Teaching Strategy on students' reading comprehension and also to find out the students' responses toward the implementation of Reciprocal Teaching Strategy in teaching reading Narrative texts. This study employed quasi experimental design. The data were obtained through the pre-test, post-test and questionnaire. There were two classes chosen as the samples; experimental and control which each of them consisted of 26 students. The participants in this study were students of 8th grade in one of Junior High School in Cimahi. The data obtained from pre-test and post-test were analyzed by using SPSS 20 and ANATES V4 for windows. The data analysis from the independent t-test showed that there was significant difference in the result of post-test means between experimental and control groups. It showed that the score of the experimental group (M=76,53) was higher than control group (M=59,61). Furthermore, based on the result of the dependent t-test showed that tobt was greater than tcrit (11,889 > 2,060) at the level of significance 0,05 indicating that the null hypothesis (H0) is rejected. It means that there was significant difference between students' pre-test and post-test of experimental group after the treatments. Moreover, the result of correlation value of effect sized was at the level of large and it indicated that Reciprocal Teaching Strategy gave large influence in improving students' reading comprehension. So that it can be stated that Reciprocal Teaching Strategy can improve students' reading comprehension. Finally, the findings from the questionnaire showed that most students gave positive responses toward this method. The students gained some benefits from this method such as helping them to comprehend the texts easily, creating an active and fun class, motivating them to participate in a group discussion, and helping them to improve their English ability. It was then recommended that Reciprocal Teaching Strategy can be used in teaching reading comprehension in different genres and levels of schooling. Keywords: Reciprocal Teaching Strategy, reading comprehension, narrative text. Tujuan utama penelitian ini adalah untuk mengamati pengaruh penerapaan strategi Reciprocal Teaching dalam pemahaman membaca siswa dan juga mencari tahu bagaimana respon siswa terhadap penerapan strategi tersebut dalam pembelajaran Reading untuk teks-teks berbentuk Naratif. Penelitian ini menggunakan desain kuasi eksperimen. Data yang digunakan dalam penelitian ini di peroleh melalui pre-test, post-test dan kuesioner. Penelitian ini mengambil dua kelas sebagai sampel, yaitu kelas eksperimen dan kelas kontrol, dimana masing-masing kelas terdiri atas 26 siswa. Partisipan dalam peneliian ini adalah siswa kelas 8 di salah satu SMP Negeri di Cimahi. Data yang diperoleh dari hasil pre-test dan post-test kemudian dianalisis menggunakan SPSS 20 dan ANATES V4 untuk Windows. Analisis data menggunakan Independent t-test menunjukan adanya perbedaan yang signifikan antara nilai rata-rata yang diperoleh dari hasil post-test kelas eksperimen dan kelas kontrol. Data menunjukan bahwa kelas eksperimen mendapakan nilai rata-rata lebih tinggi (M=76.53) dibandingkan kelas kontrol (M= 59.61). Kemudian analisis data menggunakan Dependent t-test menunjukan bahwa tobt lebih besar dari tcrit (11,889 > 2,060) pada taraf signifikan 0.05 yang mengindikasikan bahwa Hipotesis nol (H0) ditolak. Hal ini mengartikan bahwa terdapat perbedaan yang signifikan antara hasil pre-test dan post-test siswa dikelas eksperimen setelah diberikan treatments. Selain itu, analisis data yang diperoleh dari Correlation of effect size berada pada level of large, dengan kata lain strategi ini memberikan pengaruh yang besar dalam meningkatkan pemahaman membaca siswa. Terlebih, analisis data kuesioner menunjukan bahwa sebagian besar siswa memberikan respon positif terhadap strategi ini. Siswa mendapatkan banyak manfaat dari strategi tersebut, diantaranya mempermudah dalam memahami teks, membuat kelas menjadi aktif dan menyenangkan, memberi motivasi untuk berpartisipasi didalam diskusi, dan membantu meningkatkan kemampuan bahasa Inggris. Dengan demikian, strategi ini dapat direkomendasikan untuk digunakan dalam pembelajaran pemahaman membaca siswa dengan variasi teks dan tingkat pendidikan yang berbeda. Kata Kunci: Strategi Reciprocal Teaching, pemahaman membaca siswa, teks naratif.